2000
DOI: 10.1109/6979.892151
|View full text |Cite
|
Sign up to set email alerts
|

Stereo- and neural network-based pedestrian detection

Abstract: Abstract-Pedestrian detection is essential to avoid dangerous traffic situations. In this paper, we present a fast and robust algorithm for detecting pedestrians in a cluttered scene from a pair of moving cameras. This is achieved through stereo-based segmentation and neural network-based recognition. The algorithm includes three steps. First, we segment the image into sub-image object candidates using disparities discontinuity. Second, we merge and split the sub-image object candidates into sub-images that sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
157
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(159 citation statements)
references
References 29 publications
0
157
0
2
Order By: Relevance
“…Table 1 summarizes the main pedestrian detection systems, distinguished by image sensor type, area of coverage, detection performance, use of tracking, processing speed and test set, where-ever specified by the respective authors. As we will discuss in Section 6, performance comparisons are hazardous, since data sets are typically small (and diverse) (Mohan et al, 2001), Papageorgiou and Poggio (2000), Viola et al (2005), Zhao and Thorpe (2000) and often relate to single computational components (e.g. classification).…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 summarizes the main pedestrian detection systems, distinguished by image sensor type, area of coverage, detection performance, use of tracking, processing speed and test set, where-ever specified by the respective authors. As we will discuss in Section 6, performance comparisons are hazardous, since data sets are typically small (and diverse) (Mohan et al, 2001), Papageorgiou and Poggio (2000), Viola et al (2005), Zhao and Thorpe (2000) and often relate to single computational components (e.g. classification).…”
Section: Previous Workmentioning
confidence: 99%
“…The brute-force approach in combination with powerful classifiers (i.e. Mohan et al, 2001;Papageorgiou and Poggio, 2000;Zhao and Thorpe, 2000) is currently computationally too intensive for realtime application. Recently however, Viola et al (2005) demonstrated an efficient variant of the sliding window technique, which involves a detector cascade using simple appearance and motion filters (similar to the Haar-wavelets).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Zhao and Thorpe [34] use a stereo system to segment the silhouettes that are fed to a neural network that detects pedestrians. Xu and Fujimora [32] also extract body silhouettes but with a time-of-flight device.…”
Section: Previous Workmentioning
confidence: 99%